Accumulated fatigue damage assessment of side structural details in a double hull tanker based on spectral fatigue analysis approach. (1st May 2022) - Yosri, A.; Leheta, H.; Saad-Eldeen, S.; Zayed, A.
Abstract: The fatigue life of structural details in the double side of a tanker ship was investigated, employing the spectral fatigue analysis approach. The stochastic environmental loads were derived by seakeeping software based on the 3D diffraction theory, in the frequency domain, and then mapped on a structural finite element model for the ship hull. The stress response at the considered details was extracted from the finite element analysis and the accumulated damage was estimated by Palmgren-Miner's rule. The reduction of the hull girder section modulus and the deterioration of fatigue strength due to corrosion were taken into account. The influences of different wave scatter diagrams, reduction of hull girder section modulus, stress concentration factor, free corrosion S–N curve, wave direction, wave spectrum and operational profile on the accumulated fatigue damage were investigated. Highlights: Spectral fatigue analysis of structural details at the double side of a tanker is introduced. The uncertainty of the fatigue damage due to corrosion, material, operational profiles, etc. are investigated. Two loading conditions and several forward speeds are considered. The hydrodynamic pressure and structural response are evaluated using 3D potential flow theory and FEA.